International Scientific Research on Venture Capital: a Bibliometric and Mapping Analysis from the Period 1978–2020 - F. Lopez-Munoz; O. A. Eremchenko; M. A. Fernandez-Lopez; B. Rodriguez-Sanchez; F. J. Povedano-Montero (Ekonomika Nauki)
The aim of this study is to explore the relevance of scientific production on venture capital using bibliometric and mapping tools.We performed a search in Scopus, involving any document published between 1978 and 2020. We used bibliometric indicators to explore documents production, dispersion, distribution, time of duplication, and annual growth, as Price’s law of scientific literature growth, Lotka’s law, the transient index, and the Bradford model. We also calculated the participation index of the different countries and institutions. Finally, we explored the co-occurrence and thematic networks for the most frequently used terms in venture capital research through bibliometric mapping.A total of 1,230 original articles were collected from the timeframe 1978–2020. The model confirms that Price’s law is not fulfilled. Scientific production was better adjusted to linear growth (r = 0.9290) than exponential (r = 0.9161). Literature on venture capital research has increased its growth in the last 43 years at a rate of 7.9% per year, with a production that doubles its size every 9.1 years. The transience index was 79.91%, which indicates that most of the scientific production is due to a lot of authors with a small number of publications on the research topic. Bradford´s law shows that the scientific production in this area is widely distributed in multiple journals, and Lotka’s law indicates that the author’s distribution is heavily concentrated on small producers. The United States of America (USA) and the University of Pennsylvania present the highest production, contributing 31.22% and 1.63% of the total production of research on venture capital.The venture capital task has undergone a linear growth, with a very high rate of transience, which indicates the presence of numerous authors who sporadically publish on this topic. No evidence of a saturation point was observed in the scientific production analyzed, which makes it possible to conclude that the research in venture capital will continue to be in demand by the scientific community.